Bagaço de uva: aproveitamento, avaliação e aplicação em pré-mistura para bolo - Huerta, Marina Da Mota (2018)
The grape is the second fruit more produced in the world, and when destined to the industry ends up generating considerable volumes of waste. The grape marc still concentrate a large proportion of bioactive compounds and antioxidant activity in their fraction. Over the years, consumers have raised concerns about the consumption of healthy products. The objective of this work was to reuse grape pomace from the production of a flour, its evaluation and application in cake pre-mixes, in order to evaluate its contribution in physico-chemical, technological-functional and variation of parameters microbiological, physical, texture profile in prepared cakes. In addition, the grape marc flour and the pre-mix samples and their respective cakes were submitted to analysis of total phenolic compounds, total flavonoids, tannins and antioxidant activity by the ABTS method, on day 1 and after 60 days of storage, from extracts prepared with acetone or methanol, in order to evaluate the extraction efficiency. Three pre-mix treatments with different concentrations of grape pomace flour (FBU) (15, 30 and 45%) were prepared, as well as the control premix (0%), which were prepared and submitted to sensory analysis. The pre-mix with 45% of FBU obtained the highest scores for all evaluated attributes, and was selected (PMS) for analysis follow-up along with the control premix (PMC). The PMS presented higher levels of protein, lipids and total dietary fiber in relation to PMC, however the cakes prepared from the PMS presented smaller volume and greater firmness compared to the cakes prepared from the PMC. All samples showed microbiological stability. As for the content of bioactive compounds and antioxidant activity, the samples that were enriched with FBU presented considerable and higher contents than the control sample. The use of acetone as extraction solvent proved to be more effective than methanol. Thus, the production of cake premixes is an option of food rich in fibers and compounds with biological activity proven by the literature, as well as practical and versatile.